You can’t be happier than your wife. Happiness gaps and divorce - Stichnot, Holger; Guven, Cahit; Senik, Claudia (My University, 2012)
Based on three large panel surveys, this paper shows that happiness gaps between spouses are a good predictor of future divorce. The effect of happiness gaps is asymmetric: couples are more likely to break-up when the woman is the less happy partner. De facto, divorces appear to be initiated predominantly by women who are less happy than their husband. This asymmetry suggests that the effect of happiness gaps is grounded on motives of relative deprivation (i.e. comparisons of happiness between spouses) rather than on a preference for equal happiness.
Journal of Economic Behavior & Organization
Keywords: Satisfaction -- Relationships; Gender -- Gender differences; Relationships -- Divorce; Families -- Formation and dissolution; Families and relationships; Gender; Relationships; Gender; Families; Satisfaction; Divorce; Relationships; Formation and dissolution; Gender differences; Gender; Families and relationships